2011
DOI: 10.1097/cad.0b013e328349c7bb
|View full text |Cite
|
Sign up to set email alerts
|

Wound healing and catheter thrombosis after implantable venous access device placement in 266 breast cancers treated with bevacizumab therapy

Abstract: The aim of this study was to determine, in a population with metastatic breast cancer treated with bevacizumab therapy, the incidence of wound dehiscence after placement of an implantable venous access device (VAD) and to study the risk of catheter thrombosis. This study enrolled all VADs placed by 14 anesthetists between 1 January 2007 and 31 December 2009: 273 VADs in patients treated with bevacizumab therapy and 4196 VADs in patients not treated with bevacizumab therapy. In the bevacizumab therapy group, 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…However, in the NO16966 study, we observed lower or comparable rates of thrombosis compared with 1–18% in several other studies involving CVADs (where patients did not receive prophylaxis against thrombosis) (Verso et al , 2005; Karthaus et al , 2006; Fagnani et al , 2007; Ng et al , 2007; Araújo et al , 2008; Surov et al , 2008; Biffi et al , 2009; Starling et al , 2009; Beckers et al , 2010; Cavanna et al , 2010; Barbetakis et al , 2011; Kriegel et al , 2011; Saber et al , 2011). We also observed lower or comparable rates of infection than the 2.4–58.3% previously reported rates (Karthaus et al , 2006; Fagnani et al , 2007; Ng et al , 2007; Beckers et al , 2010; Cavanna et al , 2010; Barbetakis et al , 2011), although even lower infection rates of 0.4–2.5% have also been reported in some studies (Araújo et al , 2008; Biffi et al , 2009).…”
Section: Discussionsupporting
confidence: 39%
“…However, in the NO16966 study, we observed lower or comparable rates of thrombosis compared with 1–18% in several other studies involving CVADs (where patients did not receive prophylaxis against thrombosis) (Verso et al , 2005; Karthaus et al , 2006; Fagnani et al , 2007; Ng et al , 2007; Araújo et al , 2008; Surov et al , 2008; Biffi et al , 2009; Starling et al , 2009; Beckers et al , 2010; Cavanna et al , 2010; Barbetakis et al , 2011; Kriegel et al , 2011; Saber et al , 2011). We also observed lower or comparable rates of infection than the 2.4–58.3% previously reported rates (Karthaus et al , 2006; Fagnani et al , 2007; Ng et al , 2007; Beckers et al , 2010; Cavanna et al , 2010; Barbetakis et al , 2011), although even lower infection rates of 0.4–2.5% have also been reported in some studies (Araújo et al , 2008; Biffi et al , 2009).…”
Section: Discussionsupporting
confidence: 39%
“…Bevacizumab is also associated with impaired wound healing (45), likely due to the critical role of VEGF in this process. Whilst the half-life of plasma bevacizumab is 20 days, its tissue half-life is 6 weeks, hence a minimum of 28 days (preferably 6-8 weeks) should elapse between major surgery and the previous dose of bevacizumab (46).…”
Section: Bevacizumab Toxicitiesmentioning
confidence: 99%
“…After exclusion of 131 ineligible reports, we included 80 articles in the meta‐analysis (Figure 1). 7‐10,19‐93 Sixty‐nine studies with 86 cohorts included 37 000 patients who underwent TIVAP implantation without a comparison arm, 7‐10,19‐79,91‐93 whereas 11 studies (n = 2148) compared TIVAPs with external CVCs (mainly Hickman and PICC catheters) (Tables 1 and 2). 80‐90 For noncomparison studies, only two studies explicitly reported the use of anticoagulant prophylaxis (warfarin 1 mg orally daily) for VTE, 62,67 12 reported no use of any anticoagulant prophylaxis,…”
Section: Resultsmentioning
confidence: 99%
“…[80][81][82][83][84][85][86][87][88][89][90] For noncomparison studies, only two studies explicitly reported the use of anticoagulant prophylaxis (warfarin 1 mg orally daily) for VTE, 62,67 12 reported no use of any anticoagulant prophylaxis, 8,19,33,41,48,53,61,67,70,[91][92][93] and 1 used warfarin (1 mg/d) in less than 50% of their population, 64 whereas the other 54 studies did not report data for this treatment. Twenty-one studies reported the median time to occurrence of symptomatic catheter-related VTE, 8,[19][20][21]30,33,39,41,43,50,61,62,64,67,69,70,[76][77][78][79]91 which ranged from 4 to 205 days. We used the Newcastle-Ottawa scale to assess both comparison and noncomparison studies for s...…”
Section: Studies Retrieved and Characteristicsmentioning
confidence: 99%